Assessment and intervention - Scruggs, Thomas E., 1948-; Mastropieri, Margo A., 1951- (Bingley, U.K. : Emerald, 2011)
The recent emphasis on accountability in policy and practice for individuals with learning and behavioral disabilities has placed a renewed focus on issues in assessment. However, assessment in itself is of little value unless it leads to more effective and systematic interventions. In this volume, a distinguished group of international authors provide important insights on recent advances on assessment and intervention, and the relation between the two. Included in this volume are chapters on curriculum based measurement and response to intervention, dynamic assessment and working memory, diagnostic accuracy and functional diagnosis, assessment of social behavior, assessment and intervention in reading and writing, assessment and treatment of attention deficit hyperactivity disorder, and assessment and intervention in social and emotional competence and self-determination. Taken together, these chapters provide significant new information that will be of interest to graduate students, clinicians, teachers, and other professionals concerned with effective assessment and intervention for individuals with learning and behavioral disabilities.
Predictive validity of dynamic testing and working memory as it relates to reading growth in children with reading disabilities / H. Lee Swanson, Michael Orosco -- Applications of curriculum-based measures in making decisions with multiple reference points / Gerald Tindal, Joseph F.T. Nese -- Evolving standards of diagnostic accuracy in predicting and avoiding academic failure / Amanda M. VanDerHeyden -- How to use psychological tests for functional diagnosis : the case of assessment of learning disabilities / Giulia Balboni, Roberto Cubelli -- A comparison of observational techniques for assessing students' social behavior / Jugnu Agrawal, Dannette Allen-Bronaugh, Margo A. Mastropieri -- Curriculum-based measurement for beginning writers : recent developments and future directions / Kristen L. McMaster, Kristen D. Ritchey, Erica Lembke -- Issues in assessment for intervention in implementation of responsiveness to intervention models / Rollanda E. O'Connor, Victoria Sanchez -- Comorbidity between attention deficit hyperactivity disorder and reading disabilities : implications for assessment and treatment / Ana Miranda, Mar Jes{u2D73} Presentaci, Rebeca Siegenthaler, Carla Colomer, Vicente Pinto -- Assessment and intervention in self-determination / Michael L. Wehmeyer -- Success and failure with tier-2 SRSD for timed-writing tests among second-through fifth-grade students with writing and behavioral difficulties : Implications for evidence-based practice / Karin Sandmel, Kristen D. Wilson, Karen R. Harris, Kathleen Lynne Lane, Steve Graham, Wendy P. Oakes, Sharlene A. Kiuhara, Trish D. Steinbrecher -- Developing writing fluency for adolescents with disabilities / Linda H. Mason, Richard M. Kubina -- Engaging youth with disabilities in school : building and sustaining positive relationships / Elizabeth Talbott, Lisa S. Cushing -- Improving intervention effectiveness with university-public school cohort partnerships / Margo A. Mastropieri, Thomas E. Scruggs, Nicole Conners, Mary Kealy, Nancy Morrison, Tina Diamond, Terry Werner.
Keywords: Business & Economics -- Business Ethics; Business ethics; Corporate governance & responsibilities; Learning disabilities; Problem children